1998
DOI: 10.1080/0305569980240302
|View full text |Cite
|
Sign up to set email alerts
|

Co‐operation in the Countryside: small primary school clusters

Abstract: This paper examines the role and significance of co-operation (clustering) between small primary schools in rural areas across England and Wales. By increasing the range of resources available and enlarging staff and pupil peer groups, clustering can counter many of the challenges that confront curriculum delivery in small schools. However, effective inter-school liaison can be impeded by fears surrounding the loss of individual school autonomy and logistical barriers caused by the nature of rural localities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 2 publications
1
8
0
1
Order By: Relevance
“…Jointly organised excursions and programmes for pupils were common. This level of collaboration is identified as low key, without the potential loss of autonomy involved in closer links (Ribchester & Edwards, 1998;Thorpe, 1991). However, closer links were also in evidence.…”
Section: The Ethos Of Small Rural Schools -The Roots Of Collaborationmentioning
confidence: 98%
“…Jointly organised excursions and programmes for pupils were common. This level of collaboration is identified as low key, without the potential loss of autonomy involved in closer links (Ribchester & Edwards, 1998;Thorpe, 1991). However, closer links were also in evidence.…”
Section: The Ethos Of Small Rural Schools -The Roots Of Collaborationmentioning
confidence: 98%
“…It is of interest, therefore, to see how teachers in small rural schools perceive the status of their profession and the esteem in which they are held, and whether their views differ from those of teachers elsewhere. Defining esteem as the status in which an occupation is held by virtue of the personal qualities its practitioners bring to their work (Hoyle, 2001), it was hypothesised that closer links between school and community (Bell & Sigsworth, 1992;Ribchester & Edwards, 1998;Waugh, 1990) should give teachers a more positive sense of esteem as local people see their work at first hand, although Arnold (1994) and Galton and Patrick (1990) challenge this. We compared small rural and large primary school teachers' sense of responsibility to, and respect received from, sources inside and outside their schools.…”
Section: Teachers' Perceptions Of Respect In Small Rural Schoolsmentioning
confidence: 98%
“…This model would appear to have influenced recent policy on small schools (DfES, 2004a(DfES, , 2004b(DfES, , 2004c. Ribchester and Edwards (1998) surveyed 15 headteachers of small schools (90 or less) in each of 12 LEAs in England and Wales, and 58% responded. Defining 'cluster' as a 'group of proximate schools which work together and cooperate for events and activities for the mutual benefit of each of the participatory institutions' (p. 282), they distinguished usefully between developmental problems, such as tensions among governors concerning loss of autonomy, and practical problems including increases in teachers' workload, and space for visiting children.…”
Section: Small Rural Schools Working Togethermentioning
confidence: 99%
“…In their study, faculty members involved in distance education felt that the administration should help them "to interact with each other for the purpose of sharing insights and skills and to speak with a unified voice to articulate concerns" (p. 75). In a study about school clustering (i.e., schools in the same area that are cooperating for events and activities for the mutual benefit of all schools), Ribchester and Edwards (1998) found that this type of collaboration "can help to counter potential staff isolation, offering, at the very least, an opportunity to discuss problems and 'let off steam' with a wider range of teachers in similar circumstances" (p. 284).…”
Section: Collaborationmentioning
confidence: 99%